First report of the production of a potent biosurfactant with α,β-trehalose by Fusarium fujikuroi under optimized conditions of submerged fermentation - Reis,Cristiane Bianchi Loureiro dos (2018)
Abstract Biosurfactants have many advantages over synthetic surfactants but have higher production costs. Identifying microorganisms with high production capacities for these molecules and optimizing their growth conditions can reduce cost. The present work aimed to isolate and identify a fungus with high biosurfactant production capacity, optimize its growth conditions in a low cost culture medium, and characterize the chemical structure of the biosurfactant molecule. The fungal strain UFSM-BAS-01 was isolated from soil contaminated with hydrocarbons and identified as Fusarium fujikuroi. To optimize biosurfactant production, a Plackett–Burman design and a central composite rotational design were used. The variables evaluated were pH, incubation period, temperature, agitation and amount of inoculum in a liquid medium containing glucose. The partial structure of the biosurfactant molecule was identified by nuclear magnetic resonance spectrometry. F. fujikuroi reduced surface tension from 72 to 20 mN m−1 under the optimized conditions of pH 5.0, 37 °C and 7 days of incubation with 190 rpm agitation. The partial identification of the structure of the biosurfactant demonstrated the presence of an α,β-trehalose. The present study is the first report of the biosynthesis of this compound by F. fujikuroi, suggesting that the biosurfactant produced belongs to the class of trehalolipids.